Stability analysis of three-dimensional slope reinforced by natural fiber include wheat straw and bamboo - Jiahua Zhang; Yunjun Wei; Yuanlei Zhu; Daobing Zhang; Biao Zhang (Scientific Reports)
Abstract As reinforced materials, wheat straw and bamboo have many advantages of natural, green and environmental protection. For the problem about the stability of three-dimensional slope reinforced by wheat straw and bamboo natural reinforced fiber materials, the direct shear experiments were done to study the changes in shear strength of the two kinds of natural fiber reinforced soil under different reinforcement rates and curing time, respectively. The test results were introduced into the 3D stability analysis model of reinforced slopes, and the analytical solution of the stability factor was deduced by the upper bound theorem, and an optimal upper limit solution of the stability factor was solved by the exhaustive enumeration method by Matlab software. The results show that, the incorporation of wheat straw and bamboo into silty clay can significantly increase its shear strength as well as improve the stability of slopes. The stability of 3D reinforced slopes was increased by about 30% when reinforced with wheat straw at the optimal rate of 0.3%, and increased by about 120% when reinforced with bamboo at the optimal rate of 0.6%. The reinforcement effect of bamboo is better than straw, and the advantage is more obvious at smaller slope angles. In the case of optimal reinforcement, the curing time and the longitudinal size of the slope have a certain influence on the reinforcement effect. When the width-to-height ratio is B / H  ≤ 4, the three-dimensional effect of reinforced slopes is significant. When the width-to-height ratio is B / H  ≥ 5, the three-dimensional stability analysis of reinforced slopes can be simplified to two-dimensional plane strain problems. Both safety and economy of reinforced slope are considered, the reasonable design slope angle of reinforced slope is 30° to 60°, where β  = 30° is the ideal design slope angle. The research results in this paper can provide reference for the three-dimensional stability analysis of natural fiber reinforced slope.